2019
DOI: 10.3390/ma12101594
|View full text |Cite
|
Sign up to set email alerts
|

Testing and Prediction of Shear Performance for Steel Fiber Reinforced Expanded-Shale Lightweight Concrete Beams without Web Reinforcements

Abstract: In this paper, for a wide application of high-performance steel fiber reinforced expanded-shale lightweight concrete (SFRELC) in structures, the shear behavior of reinforced SFRELC beams without web reinforcements was experimentally investigated under a four-point bending test. Twenty-six beams were fabricated considering the influencing parameters of SFRELC strength, shear-span to depth ratio, longitudinal reinforcement ratio and the volume fraction of the steel fiber. The statistical analyses based on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…Typically, concrete under tension exhibits brittle failure with initial cracking when there is no reinforcement. In an effort to improve the post-cracking tensile behavior, many researchers have investigated fiber-reinforced concrete that exhibits post-cracking tensile behavior by adding fiber into the concrete mixture, and as a result, increases ductility of concrete after the crack formation [2,3,4,5,6,7,8,9,10]. Lee et al [2] developed an analysis procedure for steel-fiber-reinforced concrete (SFRC) elements subjected to shear by implementing constitutive models which are derived from the diverse embedment model (DEM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, concrete under tension exhibits brittle failure with initial cracking when there is no reinforcement. In an effort to improve the post-cracking tensile behavior, many researchers have investigated fiber-reinforced concrete that exhibits post-cracking tensile behavior by adding fiber into the concrete mixture, and as a result, increases ductility of concrete after the crack formation [2,3,4,5,6,7,8,9,10]. Lee et al [2] developed an analysis procedure for steel-fiber-reinforced concrete (SFRC) elements subjected to shear by implementing constitutive models which are derived from the diverse embedment model (DEM).…”
Section: Introductionmentioning
confidence: 99%
“…Lee and Hong [3] evaluated shear strength of ultra-high-performance fiber-reinforced concrete (UHFRC) beams without shear reinforcement. Li et al [4] investigated shear performance of SFRC beams without web reinforcement. Gali and Subramaniam as well as Husain et al [5,6] evaluated the improved ductile responses of SFRC beams and flat slabs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The loading device consisting of the steel frame, hydraulic jack, and distributive girder, and the loads were controlled by the load sensors. The mid-span deflection was measured by the electrical displacement meters installed at the mid-span, loading sections, and supports [26,37]. To verify the assumption of plane cross-section, six electrical strain meters were arranged along the depth of the mid-span cross-section.…”
Section: Test Methodsmentioning
confidence: 99%
“…The coefficient α c reflecting the uneven deformation of SFR-CRAC between cracks becomes bigger, and the coefficient ψ reflecting the uneven strain distribution of longitudinal tensile rebar among cracks becomes smaller. The predictive formulas for the maximum and average crack width on the side surface of reinforced SFR-CRAC beams at the barycenter of longitudinal tensile rebars can be written as follows [37][38][39]:…”
Section: Crack Widthmentioning
confidence: 99%
“…Li et al investigated the flexural behavior of LWAC with steel fiber and the test results showed that the steel fiber could significantly improve the compressive and flexural strength of LWAC, as well as the post-cracking behavior [21]. Li et al researched the shear performance of steel fiber-reinforced LWAC beams and reported that the shear-resistance capacity was enhanced by 25.1%, 35.9% and 43.6% with steel fiber amounts of 0.4%, 0.8% and 1.2%, respectively, as compared to those without fiber reinforcement [22]. Numerous studies showed the steel fiber's effects on the mechanical properties had significantly improved.…”
Section: Introductionmentioning
confidence: 99%